A GIS-based multi-criteria evaluation of landfill site selection in the region of Hodna, Algeria - Abderazak Magoura; Salim Dehimi; Ali Redjem (Brawijaya University, 2023)
In Algeria, solid waste management (SWM) is considered a major problem; most of this waste is dumped in landfills without any control. The Algerian authorities have developed a national strategy for the integrated management of urban solid waste by 2035 by working on the implementation, development and equipping of technical landfill centers (TLC). Therefore, the aim of this study was to help local authorities in choosing the optimal locations for the completion of the proposed TLC between municipalities. This research used a combination of the multi-criteria decision aid (MCDA) and geographic information systems (GIS). It combines two aggregation methods: Linear Combination of Weights (WCL) and Criteria Weighting. The analytical hierarchy process (AHP) pair-wise comparison method was applied for assigning weights to the 11 criteria that were divided into environmental, social, and economic criteria according to previous studies in the field and the characteristics of the HODNA area. The results showed that 22.56% is the most suitable location for a landfill site, especially on the southeastern side, while 20.70% was suitable and 18.40% was moderately suitable. Finally, the process of assessing the spatial suitability of public emptying sites based on the results obtained in the final digital map,4.76% of the landfill sites are located in inappropriate areas, 14.29% are located in less suitable areas, 33.33% are located in suitable areas, 33.33% are located in moderately suitable areas and 14.29% are located in very suitable areas.